Cysticercosis Cellulosae in Labial Mucosa: A Rare Case Report - Raghavendra M Shetty; Ramprasad; Anshu Kalra; Shirish Goyal; B M Sachin; Sunaina Shetty; Pravin Lambade; Abhijeet Deoghare (Wolters Kluwer Medknow Publications, 2010)
Cysticercosis is a condition in which a human acts as the intermediate host of Taenia solium, a pork tapeworm. The larvae infestation sites frequently include cerebral tissue, ocular organs and muscles. The present case report describes a rare incidence of cysticercosis cellulosae in the labial mucosa of upper lip